Corrugated SCR (Selective Catalytic Reduction) catalyst as well as preparation method and application thereof

By coating molecular sieve catalysts during corrugated molding, the preparation process of SCR catalysts is simplified, and the problems of high energy consumption and difficult to meet the hydrothermal aging requirements of National VI standards in the prior art are solved, thereby increasing the high temperature intensity of the catalyst and maintaining the NOx conversion rate.

CN119657209APending Publication Date: 2025-03-21QINGDAO HUASHIJIE ENVIRONMENT TECHNOLOGY CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311210200.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-19
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing SCR catalyst molding technology consumes high energy and is difficult to meet the hydrothermal aging requirements of above 700°C in the National VI standard, and it is difficult to achieve a simple, efficient and low-energy-consuming preparation process.

Method used

Fibre paper is used to coat molecular sieve catalysts during corrugated molding, and the corrugated SCR catalyst is prepared through one-time molding, which simplifies the preparation process and reduces production energy consumption.

Benefits of technology

It has achieved high temperature strength improvement of the catalyst, maintained a high NOx conversion rate, extended the service life of the catalyst, and is suitable for diesel engines under the National VI standard.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119657209A_ABST
    Figure CN119657209A_ABST
Patent Text Reader

Abstract

The invention provides a corrugated SCR (Selective Catalytic Reduction) catalyst as well as a preparation method and application thereof. The preparation method of the corrugated SCR catalyst comprises the following steps: uniformly mixing a molecular sieve, a copper source and water, heating and stirring for ion exchange, and then adding a binder, a dispersant, an auxiliary agent and water to prepare catalyst coating slurry; respectively carrying out first coating on fiber paper and corrugation by adopting the obtained catalyst coating slurry, and then compounding the fiber paper and the corrugation which are subjected to the first coating, so as to prepare the corrugated paper; the preparation of the corrugations comprises the following steps: pressing fiber paper into the corrugations through corrugating rollers which are arranged in pairs; and carrying out second coating on the prepared corrugated paper by using the obtained catalyst coating slurry, and then drying and roasting to obtain the corrugated paper. The corrugated SCR catalyst is prepared by the preparation method, and is suitable for national sixth diesel engines. The SCR catalyst is prepared by adopting a one-step forming process, and the obtained catalyst is low in density, high in catalytic activity, low in cost and suitable for industrial popularization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts and preparation thereof, and in particular relates to a corrugated SCR catalyst and a preparation method and application thereof. Background Art

[0002] SCR catalyst has the performance of selective catalytic reduction and is often used in denitrification process. By adding ammonia to the flue gas, the fixed reaction points on the SCR catalyst are reduced to NO x It reacts with NH3 to generate N2 and H2O, thus achieving the denitration effect. In addition, the SCR denitration catalyst can not only reduce harmful substances in tail gas such as sulfate and carbon dioxide, but also achieve the environmental protection effect of purifying exhaust gas. It is a widely used environmental protection product.

[0003] The existing SCR catalyst molding technology basically involves making a carrier first and then coating the catalyst, which is a two-step process. The preparation process consumes a lot of energy. In addition, the current corrugated SCR catalyst is mainly based on the National V standard, which is difficult to meet the hydrothermal aging requirements of the National VI standard above 700°C. With people's increasing attention to environmental protection and the increasing emission levels of vehicles, it is urgent to develop a simple, efficient and low-energy process to prepare SCR catalysts with high temperature strength that can meet the working conditions of the National VI diesel engine.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The object of the present invention is to provide a corrugated SCR catalyst and a preparation method and application thereof to solve the above problems.

[0006] In order to achieve the above objectives, the present invention particularly adopts the following technical solutions:

[0007] A method for preparing a corrugated SCR catalyst comprises the following steps:

[0008] S1: Mix the molecular sieve, copper source and water evenly, heat and stir to perform ion exchange, and then add a binder, a dispersant, an additive and water to prepare a catalyst coating slurry;

[0009] S2: using the catalyst coating slurry obtained in S1 to perform a first coating on the fiber paper and the corrugated paper respectively, and then compounding the fiber paper and the corrugated paper after the first coating to prepare corrugated paper;

[0010] The preparation of the corrugated paper includes: pressing the fiber paper into corrugated paper through a pair of corrugated rollers;

[0011] S3: The catalyst coating slurry obtained in S1 is used to perform a second coating on the corrugated paper obtained in S2, and then dried and calcined to obtain the product.

[0012] Preferably, S1 satisfies one or more of the following conditions:

[0013] a. The molecular sieve comprises SSZ-13 or SAPO-34;

[0014] b. The copper source includes one or more of copper sulfate, copper acetate, copper nitrate and copper chloride;

[0015] c. The target temperature of the heating is 30-80°C;

[0016] d. The stirring rate is 20-200r / min;

[0017] e. The ion exchange time is 0.5-3h.

[0018] Preferably, S1 also satisfies one or more of the following conditions:

[0019] f. The mass ratio of water, molecular sieve and copper source is 100:20-50:0-5; too high a copper source content will lead to poor dispersion, polymerization of copper ions and decreased catalytic performance, while too low a copper source content will lead to too low a free copper content after ion exchange, insufficient catalytic active sites and decreased catalytic performance.

[0020] g. The binder includes one or more of silica sol, alumina sol, silica-alumina sol, titanium sol and zirconium sol;

[0021] h. The dispersant comprises one or more of alkylbenzene sulfonates, fatty alcohol sulfates, polyethylene glycols, polyvinyl alcohol, polyols, alkylolamides, and imidazolines;

[0022] i. The additive includes one or more of ammonia, ethanolamine, resin, ethylene glycol, polyethylene glycol, glycerol, butanol, isobutanol, acetylenes, ethers, silicones, mineral oils, polyethers, polycarboxylates, and polyacrylic acids;

[0023] Further preferably, S1 further satisfies one or more of the following conditions:

[0024] j. The amount of the dispersant is 0.1-2% of the mass of the molecular sieve;

[0025] k. The dosage of the auxiliary agent is 0.1-9% of the mass of the molecular sieve.

[0026] The combination of dispersants and additives can highly disperse the catalyst slurry, so that the catalyst slurry is evenly coated on the surface of the fiber paper carrier, increasing the adhesion between the catalyst and the fiber paper. The catalyst has strong adhesion to the surface of the fiber paper and will not crack or fall off.

[0027] Preferably, S2 satisfies one or more of the following conditions:

[0028] l. The fiber paper is selected from one or more inorganic fiber papers;

[0029] m. The first coating is carried out by dipping at 50-60 ° C;

[0030] The first coating is carried out at a slurry temperature of 50-60°C, preferably 60°C, at which the active components in the coating slurry are better dispersed, which is beneficial to improving the activity of the catalyst. Compared with traditional organic adhesive bonding, the corrugated paper and fiber paper wet pulp composite will leave macroscopic and microscopic pore structures on the surface after drying, which is beneficial to improve the slurry bonding degree of the subsequent second coating;

[0031] n. The height of the corrugated roller is 1.0-5.0 mm.

[0032] Further preferably, S2 also satisfies one or more of the following conditions:

[0033] o. The fiber paper comprises high silica fiber paper;

[0034] p. The compounding includes heat baking.

[0035] Preferably, S3 satisfies one or more of the following conditions:

[0036] q. The second coating is vacuum coating; the vacuum coating process and negative pressure coating process can remove the macroscopic and microscopic holes left by the first coating, improve the bonding strength between the first coating and the second coating, enhance the catalyst's anti-wear performance, and increase the catalyst's service life;

[0037] r. The drying includes one or more of vacuum drying, hot air drying, natural air drying, and microwave drying;

[0038] s. The calcination temperature is 450-600°C and the calcination time is 2-6h.

[0039] If the calcination temperature is too high, the active component Cu will polymerize at high temperature, and the dispersion will decrease, resulting in performance degradation. If the calcination temperature is too low, the copper source and the molecular sieve ion exchange will not be cured at high temperature, resulting in a decrease in high temperature performance.

[0040] The invention provides a corrugated SCR catalyst, which is prepared by the preparation method.

[0041] The present invention also provides an application of the corrugated SCR catalyst, and the corrugated SCR catalyst is suitable for National VI diesel engines.

[0042] Preferably, the corrugated SCR catalyst is applied to a National VI diesel engine for selective catalytic reduction of nitrogen oxides, and the reaction conditions are: the reaction temperature is controlled in the range of 100 to 600°C, ammonia is used as a reducing agent, NO x Concentration is 100-1000ppm, NH3 / NO x The ratio is in the range of 1.0-1.1, and the airspeed is 30k-50kh -1 ;

[0043] Preferably, the hydrothermal aging conditions of the corrugated SCR catalyst are: NO x Concentration is 500ppm, NH3 / NO x The ratio is 1.0 and the airspeed is 50kh -1 , H2O content is 10%, O2 content is 8%, temperature is 750℃, and time is 10h.

[0044] Beneficial effects of the present invention:

[0045] The preparation method provided by the present invention is different from the preparation of conventional SCR catalysts. The present invention adopts fiber paper to coat molecular sieve catalysts during the corrugated forming process, and prepares corrugated SCR catalysts through one-time forming, which simplifies the preparation process and greatly reduces production energy consumption.

[0046] The coating amount and volume density of the prepared corrugated SCR catalyst are reduced, the high temperature strength is significantly improved, and a high NO content is maintained in both the fresh and aged states. x conversion rate, showing better catalytic activity.

[0047] The high-temperature strength of the corrugated SCR catalyst provided by the present invention is significantly improved, and is more suitable for the higher-temperature hydrothermal aging requirements of diesel engines that meet the National VI standard. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0049] Figure 1 This is a schematic diagram of the process flow of preparing corrugated paper in Example 1;

[0050] Figure 2 The catalysts provided in the examples and comparative examples react with NO in a fresh state. x Conversion rate test chart;

[0051] Figure 3The catalysts provided in the embodiments and comparative examples are oxidized to NO in an aged state. x Conversion rate test chart. DETAILED DESCRIPTION

[0052] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0053] Example 1

[0054] According to the method provided by the present invention, the corrugated SCR catalyst is prepared, and the specific steps are as follows:

[0055] S1. Preparation of catalyst coating slurry:

[0056] Weigh 20 kg of SSZ-13 molecular sieve, add 1.0 kg of copper sulfate and 60 kg of deionized water, stir at 60 ° C, stir at 50 r / min, perform ion exchange for 1 hour, then add 10 kg of silica sol, 1 kg of ammonia water, 0.4 kg of ethanolamine, 60 g of polyethylene glycol and 120 g of silicone defoamer, stir evenly to obtain a catalyst coating slurry;

[0057] S2. Preparation of corrugated National VI diesel engine SCR catalyst:

[0058] (1) High silica fiber paper is pressed into corrugated paper through a 2.2 mm corrugated roller, and then impregnated with glass fiber paper into the catalyst coating slurry obtained in S1 to achieve the first coating, and then dried and compounded to produce corrugated paper; the schematic diagram of the preparation process is shown in Figure 1 As shown;

[0059] (2) The corrugated paper in (1) is made into Catalyst precursors;

[0060] (3) The catalyst precursor in (2) is immersed in the catalyst coating slurry of S1 for a second coating, and then microwave dried for 2 hours and calcined at 500° C. for 4 hours to obtain a corrugated SCR catalyst suitable for National VI diesel engines.

[0061] The corrugated SCR catalyst prepared in this embodiment has a bulk density of 208 g / L, and the contents of SSZ-13 and Cu in the overall composition of the catalyst are 123 g / L and 4.2 g / L, respectively.

[0062] Example 2

[0063] According to the method provided by the present invention, the corrugated SCR catalyst is prepared, and the specific steps are as follows:

[0064] S1. Preparation of catalyst coating slurry:

[0065] Weigh 20 kg of SSZ-13 molecular sieve, add 1.5 kg of copper acetate and 65 kg of deionized water, stir at 70 ° C, stir at 80 r / min, perform ion exchange for 2.5 hours, then add 10 kg of silica sol, 0.8 kg of ammonia water, 0.35 kg of ethanolamine, 65 g of organosilicon dispersant and 120 g of mineral oil defoamer, stir evenly to obtain a catalyst coating slurry;

[0066] S2. Preparation of corrugated National VI diesel engine SCR catalyst:

[0067] (1) The high-silica fiber paper is pressed into corrugated paper by a 1.5 mm corrugated roller, and then impregnated together with the high-silica fiber paper flat paper into the catalyst coating slurry obtained in S1 to achieve a first coating, and then dried and compounded to produce corrugated paper;

[0068] (2) The corrugated paper in (1) is made into Catalyst precursors;

[0069] (3) The catalyst precursor in (2) is immersed in the catalyst coating slurry of S1 for a second coating, and then vacuum dried for 1.5 hours and calcined at 550° C. for 5 hours to obtain a corrugated SCR catalyst suitable for National VI diesel engines.

[0070] The corrugated SCR catalyst prepared in this embodiment has a bulk density of 210 g / L, and the contents of SSZ-13 and Cu in the overall composition of the catalyst are 131 g / L and 5.8 g / L, respectively.

[0071] Example 3

[0072] According to the method provided by the present invention, the corrugated SCR catalyst is prepared, and the specific steps are as follows:

[0073] S1. Preparation of catalyst coating slurry:

[0074] Weigh 20 kg of SAPO-34 molecular sieve, add 1.2 kg of copper chloride and 68 kg of deionized water, stir at 50 ° C, stir at 100 r / min, perform ion exchange for 3 hours, then add 8 kg of silica sol, 0.8 kg of ammonia water, 0.35 kg of ethanolamine, 55 g of polycarboxylate dispersant and 110 g of ether defoamer, stir evenly to obtain a catalyst coating slurry;

[0075] S2. Preparation of corrugated National VI diesel engine SCR catalyst:

[0076] (1) High silica fiber paper is pressed into corrugated paper by a 2.7 mm corrugated roller, and then impregnated together with ceramic fiber flat paper into the catalyst coating slurry obtained in S1 to achieve a first coating, and then dried and compounded to produce corrugated paper;

[0077] (2) The corrugated paper in (1) is made into Catalyst precursors;

[0078] (3) The catalyst precursor in (2) is immersed in the catalyst coating slurry of S1 for a second coating, and then dried by hot air for 3 hours and calcined at 580° C. for 3 hours to obtain a corrugated SCR catalyst suitable for National VI diesel engines.

[0079] The corrugated SCR catalyst prepared in this embodiment has a bulk density of 218 g / L, and the contents of SAPO-34 and Cu in the overall catalyst composition are 118 g / L and 5.2 g / L, respectively.

[0080] Comparative Example 1

[0081] The difference from Example 2 is that the high-silica fiber paper used in step (1) of S2 is replaced by glass fiber paper.

[0082] Comparative Example 2

[0083] The difference from Example 2 is that the high-silica fiber paper used in step (1) of S2 is replaced by basalt fiber paper.

[0084] Comparative Example 3

[0085] The difference from Example 2 is that the high-silica fiber paper used in step (1) of S2 is replaced by ceramic fiber paper.

[0086] Comparative Example 4

[0087] The difference from Example 2 is that:

[0088] Step (1) of S2 is: pressing the high-silica fiber paper through a 1.8 mm corrugating roller to form corrugated paper, then impregnating the high-silica fiber paper and the flat paper into silica sol, and then drying and compounding to produce corrugated paper.

[0089] The performance test of the catalysts prepared in Examples 1-3 and Comparative Examples 1-4 was carried out. A catalyst sample with a volume of 8.1 mL was taken and the concentrations of the catalyst inlet and outlet before and after the reaction were measured using a flue gas analyzer at the programmed temperature. The test conditions were: NO x The concentration is 1000mg / m3, the ammonia nitrogen molar ratio is 1:1, the O2vol% is 6%, and the air velocity is 35Kh -1The fresh catalyst was subjected to hydrothermal aging to obtain an aged catalyst under the following conditions: NO x Concentration is 500ppm, NH3 / NO x The ratio is 1.0 and the airspeed is 50kh -1 , H2O content 10%, O2 content 8%, temperature 750℃, time 10h. Calculate the catalytic activity of the SCR catalyst and test the catalyst for NO under different conditions of fresh and aged state. x The conversion efficiency is shown in Table 1. Figure 2 , Figure 3 As shown, Figure 2 The fresh catalyst reacts with NO x Conversion rate test chart, Figure 3 The aging catalyst has a x Conversion rate test chart.

[0090] Table 1: Catalytic performance of the examples and comparative examples for NO under different conditions x Conversion efficiency test results table

[0091]

[0092] As shown in Table 1, the catalyst provided by the present invention has a x The conversion efficiency, i.e., the catalytic performance, is significantly higher than that of the comparative example as a whole, especially in the fresh state at high temperature of 600° C. and the aged state, the catalyst provided by the present invention exhibits higher catalytic activity and stronger stability and durability.

[0093] By comparing Example 2 with Comparative Examples 1, 2, and 3, it can be seen that when other conditions are the same, only the type of fiber used is changed, and the performance of the catalyst obtained is significantly different. Compared with conventional fibers in the field such as glass fiber, basalt fiber, and ceramic fiber, the catalyst prepared by the process of the present invention using high-silica fiber combined with the process of the present invention is more superior in catalytic activity, durability, and stability, whether in a fresh state or an aged state, whether in a low-temperature or high-temperature state, especially the catalytic activity performance in a high-temperature state, indicating that it is more suitable for the higher-temperature hydrothermal aging requirements of diesel engines that meet the National VI standard.

[0094] By comparing Comparative Example 4 with Example 2, and Comparative Example 4 with Comparative Examples 1-3, it can be seen that, under the same other conditions, although Comparative Example 4 uses high-silica fiber, it is not coated with catalyst coating slurry during the first coating, but coated with silica sol. As a result, the catalytic performance of Comparative Example 4 is slightly better than that of Comparative Examples 1-3 due to the use of high-silica fiber, but is obviously worse than that of the catalyst of the present invention, especially at high temperature and in the aged state. xThe sharp drop in conversion rate indicates that it is not resistant to high temperatures and has poor durability and stability. This means that if conventional fibers are simply replaced with high-silica fibers without making creative improvements in process design, the performance of the resulting catalyst will not be ideal.

[0095] The mechanical properties of the catalysts prepared in Examples 1-3 and Comparative Examples 1-4 were tested in different states, namely, fresh state and aged state. The results are shown in Table 2.

[0096] Table 2 Mechanical properties test results of catalysts in different states for examples and comparative examples

[0097]

[0098] It can be seen from Table 2 that the strength of Comparative Examples 1-3 decreases significantly after aging, because the ceramic fiber and basalt fiber have impurities, which leads to a significant decrease in performance after aging, and the glass fiber undergoes a glass transition after high temperature. The mechanical properties of the catalyst prepared by the high-silica fiber in the embodiment of the present invention remain excellent at high temperature and in the aged state, and can be used as a supporting material for the corrugated National VI diesel engine SCR catalyst. The mechanical strength of Comparative Example 4 is acceptable, but its density is too high, which may affect the catalytic activity, and the relevant data in Table 1 above have confirmed this.

[0099] In summary, the catalytic performance and mechanical properties of the corrugated SCR catalyst provided by the present invention are significantly better than those of the prior art, especially after hydrothermal aging, the performance is significantly improved.

[0100] Please note that the technical features of the above embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. The above embodiments only express several implementation methods of the present application, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several variations and improvements can be made, which all belong to the scope of protection of the present application. Therefore, the scope of protection of the patent in this application shall be based on the attached claims.

Claims

1. A method for preparing a corrugated SCR catalyst, characterized in that: The steps include: S1: Mix the molecular sieve, copper source and water evenly, heat and stir to perform ion exchange, and then add a binder, a dispersant, an additive and water to prepare a catalyst coating slurry; S2: using the catalyst coating slurry obtained in S1 to perform a first coating on the fiber paper and the corrugated paper respectively, and then compounding the fiber paper and the corrugated paper after the first coating to prepare corrugated paper; The preparation of the corrugated paper includes: pressing the fiber paper into corrugated paper through a pair of corrugated rollers; S3: The catalyst coating slurry obtained in S1 is used to perform a second coating on the corrugated paper obtained in S2, and then dried and calcined to obtain the product.

2. The preparation method according to claim 1, characterized in that: S1 satisfies one or more of the following conditions: a. The molecular sieve comprises SSZ-13 or SAPO-34; b. The copper source includes one or more of copper sulfate, copper acetate, copper nitrate and copper chloride; c. The target temperature of the heating is 30-80°C; d. The stirring rate is 20-200r / min; e. The ion exchange time is 0.5-3h.

3. The preparation method according to claim 1, characterized in that: The S1 also satisfies one or more of the following conditions: f. The mass ratio of water, molecular sieve and copper source is 100:20-50:0-5; g. The binder includes one or more of silica sol, alumina sol, silica-alumina sol, titanium sol and zirconium sol; h. The dispersant comprises one or more of alkylbenzene sulfonates, fatty alcohol sulfates, polyethylene glycols, polyvinyl alcohol, polyols, alkylolamides, and imidazolines; i. The auxiliary agent includes one or more of ammonia, ethanolamine, resin, ethylene glycol, polyethylene glycol, glycerol, butanol, isobutanol, acetylenes, ethers, silicone, mineral oil, polyethers, polycarboxylates, and polyacrylic acids.

4. The preparation method according to any one of claims 1 to 3, characterized in that The S1 also satisfies one or more of the following conditions: j. The amount of the dispersant is 0.1-2% of the mass of the molecular sieve; k. The dosage of the auxiliary agent is 0.1-9% of the mass of the molecular sieve.

5. The preparation method according to claim 1, characterized in that: S2 satisfies one or more of the following conditions: l. The fiber paper is selected from one or more inorganic fiber papers; m. The first coating is carried out by dipping at 50-60 ° C; n. The height of the corrugated roller is 1.0-5.0 mm.

6. The preparation method according to claim 1 or 5, characterized in that: S2 also satisfies one or more of the following conditions: o. The fiber paper comprises high silica fiber paper; p. The compounding includes heat baking.

7. The preparation method according to claim 1, characterized in that: The S3 satisfies one or more of the following conditions: q. the second coating is vacuum coating; r. The drying includes one or more of vacuum drying, hot air drying, natural air drying, and microwave drying; s. The calcination temperature is 450-600°C and the calcination time is 2-6h.

8. A corrugated SCR catalyst, characterized in that: Prepared by the preparation method according to any one of claims 1 to 7.

9. An application of the corrugated SCR catalyst as claimed in claim 8, characterized in that: The corrugated SCR catalyst is suitable for National VI diesel engines.

10. The use according to claim 9, characterized in that: The corrugated SCR catalyst is applied to a National VI diesel engine for selective catalytic reduction of nitrogen oxides, and the reaction conditions are: the reaction temperature is controlled in the range of 100 to 600° C., ammonia is used as a reducing agent, NO x Concentration is 100-1000ppm, NH3 / NO x The ratio is in the range of 1.0-1.1, and the airspeed is 30k-50kh -1 ; Preferably, the hydrothermal aging conditions of the corrugated SCR catalyst are: NO x Concentration is 500ppm, NH3 / NO x The ratio is 1.0 and the airspeed is 50kh -1 , H2O content is 10%, O2 content is 8%, temperature is 750℃, and time is 10h.

Citation Information

Cited By

  • Preparation method of medium-temperature corrugated plate SCR (Selective Catalytic Reduction) denitration catalyst

    CN121103348A